Student Assessment in Higher Education: A Comparative Study of Russia and Indonesia - Elena, Dimitruk; Untari , Sri; Al-Atok, A Rosyid; Nafsiyah , Fitrotun (Edukasi, 2024)
This paper presents a comparative study of student assessment approaches in higher education institutions in Russia and Indonesia. The purpose of the study is to explore the methods, criteria, and frameworks used to evaluate student performance in both countries. The research methods used in this article include a descriptive qualitative approach and library research. The study employed a combination of document analysis and thematic coding to analyze the data, focusing on how educational policies, cultural contexts, and institutional practices shape assessment approaches. In Russia, the centralized governance system and long-standing academic traditions significantly influence assessment methods, while Indonesia’s decentralized educational structure and diverse cultural heritage lead to varied and flexible evaluation practices. The findings highlight both the strengths and weaknesses of each country’s assessment systems, emphasizing areas such as standardization, student engagement, and fairness in evaluations. The study concludes that while the two countries have distinct approaches, there are valuable insights each can gain from the other’s experiences. This research contributes to the global dialogue on improving student assessment practices by demonstrating how cultural and contextual factors must be considered to develop more effective and equitable evaluation systems.